The work-family challenge : rethinking employment - Lewis, Suzan; Lewis, Jeremy (Sage Publications, 1996)
In The Work-Family Challenge contributors from the United Kingdom, Europe and the United States explore the possibilities of challenging traditional employment structures to take account of contemporary work and family realities. They take a critical look at the notion of f̀amily-friendly' employment, and explore ways in which the rapidly changing needs of both organizations and the workforce can be met. The volume argues that real progress requires moving the focus from specific policies and practices towards more systemic organizational change. It examines the contexts and opportunities - gl.